High-fidelity contingency trajectory design and analysis for NASA's near-earth asteroid (NEA) Scout solar sail Mission. (June 2019) - Pezent, James; Sood, Rohan; Heaton, Andrew
Abstract: Exploratory missions to investigate accessible Near Earth Asteroids (NEAs) can benefit from leveraging dynamics associated with a solar sail-based spacecraft. As a part of this effort, NEA Scout is a solar sail mission designed to propel a 6U CubeSat by harnessing solar radiation pressure from the Sun. The spacecraft will be launched as a secondary payload on NASA's Space Launch System (SLS) Exploration Mission One (EM-1). As the launch of EM-1 has recently been rescheduled for December 2019, alternative target NEAs are identified. Additionally, solar sail-based trajectories for the NEA Scout mission also need to be reevaluated. In this study, high-fidelity trajectories for the NEA Scout mission are investigated for varying launch dates under the assumption of the failure of a critical propulsive maneuver. Furthermore, feasible trajectory solutions are presented for multiple candidate asteroids.